Effects of gas pressure and catheter length on the breakup of discontinuous NiTi droplets in electrode induction melting gas atomization - Bo Xie; Wei Li; Xinyu Liu; Ge Zhou; Sanchao Zhao; Yongsheng Liu; Wang Wu; Dong Lu; Weixing Peng (Materials Research Express, 2024)
NiTi powders used for selective laser melting have here been fabricated by the breakup of discontinuous droplets in electrode induction melting gas atomization (EIGA). The morphology, particle size distribution, and hollow ratio of the powder were characterized by scanning electron microscopy (SEM), laser particle size analyzer, and computed tomography (CT), respectively. The effects of gas pressure and catheter length on the particle size distribution and powder morphology were then studied. Furthermore, the effects of the classifier wheel speed on the particle size distribution and yield of the 15–53 μ m powder in the classification process were also analyzed. The results showed that the average particle size (D50) of the NiTi powder first decreased and, thereafter, increased as the atomization gas pressure increased. This was also the situation with catheter length. Also, the yield of the 15–53 μ m powder increased with an increase in the classifier wheel speed. The optimum parameters were a gas atomization pressure of 5 MPa, a tension length of 28 mm, and a classifier wheel speed of 660 r min ^−1 . For this optimized condition, the D50 value and the yield of the NiTi powder were 57.54 μ m and 46.4%. In addition, the flowability, hollow ratio, and oxygen content were 15.8 s/50 g, 0.31%, and 450 ppm, respectively.